Analisis Fundamental Makro, Struktur Modal Terhadap Nilai Perusahaan Dengan Arus Kas, Kinerja Keuangan, Karakteristik Perusahaan Sebagai Variabel Intervening Studi Kasus : Pada Perusahaan Tambang Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2023 - Hwihanus Hwihanus; Zufi Yustika Magitasiwi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research aims to determine the results of Macro Fundamental Analysis, Capital Structure on Company Value with Cash Flow, Financial Performance, Company Characteristics as Intervening Variables in mining companies. This research uses quantitative methods with secondary data originating from the financial reports of companies listed on the IDX which are then tested using SmartPLS software. The results of this research show that what has a relationship between variables in Macro Fundamental Analysis, Capital Structure on Company Value with Cash Flow, Financial Performance, Company Characteristics as Intervening Variables is macro fundamentals with financial performance, company characteristics with financial performance and company value, and performance finances with company value.